Penggunaan Media Buku Cerita Ramah Anak Untuk Meningkatkan Kemampuan Bahasa Lisan Pada Anak PAUD St. Paulus Terpadu Kotakadhe - Lero, Maria Vinsensia; Laksana, Dek Ngurah Laba; Ita, Efrida; Ngura, Elisabeth Tantiana (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study aims to improve the oral language skills of group B children at PAUD St. Paulus Terpadu Kotakadhe through the use of child-friendly storybook media. The method used is Class Action Research (PTK) which is carried out in two cycles, each of which includes the stages of planning, implementation, observation, and reflection. The subjects of the study were 15 children. Data collection techniques are carried out through structured observation, anecdotal notes, and documentation, with qualitative and quantitative descriptive data analysis. The results of the study showed a significant improvement in children's speaking skills from pre-action to cycle I and cycle II. In cycle I, the child begins to show the courage to speak and is able to retell simple stories, although still limited in sentence structure and vocabulary. Improvement in strategy in cycle II resulted in further improvement, with children showing more fluent speaking skills, richer vocabulary, and higher confidence. The percentage of achievement of speech development indicators increased from 46% (pre-action) to 73% (cycle I) and 93% (cycle II). These results show that child-friendly storybook media is effective in improving early childhood oral language skills. This study recommends that PAUD teachers integrate child-friendly book-based storytelling sessions into daily learning activities.